Pengaruh Sistem Informasi Manajemen Berbasis Komputer Terhadap Kinerja Pegawai Pada Koperasi Pegawai Negeri (KPN) Bina Sejahtera Kabupaten Badung Tahun 2016 - Sujata, Pande Putu Aditya; Noak, Piers Andreas; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2016)
ABSTRACT Civil Servants Cooperatives (KPN) Bina Sejahtera in supporting and operating their business needed of employee performance with the participation of computer-based management information system. This study has a purpose, that is to analyze the influence of computer-based management information system on the performance of employees at KPN Bina Sejahtera Badung regency. This research was conducted in KPN Bina Sejahtera using census method (total sampling) of 50 respondents through a simple linear regression analysis. This analysis has a result, that is to prove that computer-based management information system of positive and significant effect on employee performance at KPN Bina Sejahtera Badung regency which is indicated by the value of determination total of 0.189 which means 18.9% influenced by the performance management information system remaining 81.1% influenced by other factors. The advice that can be given is the need for the involvement of managerial in increase the application field of computer-based management information system, so that the employees do not feel complicated in completing the task and responsibility of the individual concerned. Keywords: Management Information Systems, Employee Performance